2011
DOI: 10.1007/s10533-011-9604-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased organic carbon concentrations in Estonian rivers in the period 1992–2007 as affected by deepening droughts

Abstract: There are 10,091 km 2 of peatlands in Estonia and human activities may have changed the role of northern peatlands from global sinks to global sources of carbon. The aim of this work was to explain the changes in organic carbon exports from eleven Estonian rivers in the period 1992-2007 in terms of land use change, climate change quantified by trends in stream-water discharge and hydrological droughts and reductions in atmospheric sulfate quantified by change in water chemistry. Direct TOC (total organic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…During the 1900 s, drought frequency in Europe generally appears to have increased (Worrall et al , ; Pärn and Mander, ), although the temporal scale of this dynamic remains unclear. For example, an earlier onset of spring warming has already been noted during the 19th century in the southern part of the Baltic sea (Tarand and Nordli, 2001), implying better conditions for the development of water deficit in forest fuels during the fire season.…”
Section: Discussionmentioning
confidence: 99%
“…During the 1900 s, drought frequency in Europe generally appears to have increased (Worrall et al , ; Pärn and Mander, ), although the temporal scale of this dynamic remains unclear. For example, an earlier onset of spring warming has already been noted during the 19th century in the southern part of the Baltic sea (Tarand and Nordli, 2001), implying better conditions for the development of water deficit in forest fuels during the fire season.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning methodological issues, some studies follow tendencies directly in the surrogate parameter as such [26,60,61,65,72,77] but a common practice is to establish an empirical correlation between the parameter values and OC concentrations using data simultaneously measured over a short period of time [29,38,48,50,53,61] and discuss tendencies, causes, etc. in terms of OC concentrations.…”
Section: Organic Carbon Concentration Measurementsmentioning
confidence: 99%
“…Even extrapolating synchronous data between close systems seems questionable. For instance, Pärn and Mander showed that TOC and COD for rivers in Estonia, a small country, showed different Spearman's correlation coefficients depending on the area considered (much higher in the North than in the South) [26].…”
Section: Organic Carbon Concentration Measurementsmentioning
confidence: 99%
“…It has been hypothesized that this “browning” trend may be associated with drivers of global change, including altered land-use [12], precipitation patterns [13], temperatures [14], and atmospheric deposition [15]. Regardless of the controlling factors, there is considerable uncertainty about how aquatic ecosystems will respond to increasing inputs of terrestrial DOC [16].…”
Section: Introductionmentioning
confidence: 99%